PENTINGNYA INTEGRITAS DAI DALAM MENYAMPAIKAN DAKWAH DI PENGAJIAN MASJID NURUL HUDA GANTAR - Nurmaidah; Alfi Satria (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2023)
The community is a partner as well as a target in the process of da'wah activities who have great hopes for the da'wah as the executor of the da'wah, although not all of the hopes of the community are in the dai, but the weaknesses and shortcomings that the dai has as an ordinary human being are not a reason for the dai to continue to introspect himself to be better. This is because the preacher must realize that he is a role model for the people, who will be a source of reference for the people in solving religious and social problems, because personality integrity is an important factor that can support the success of da'wah. The purpose of research in this thesis is to understand the integrity and supporting factors and inhibiting factors of the Da'i in Conveying Da'wah at the Nurul Huda Gantar Mosque Recitation. This study uses qualitative research methods. The population of this study is the Nurul Huda Gantar Mosque Management, Dai' and the community around the Nurul Huda Gantar Mosque. Then the samples are representatives of the Nurul Huda Gantar Mosque Management, Dai' and the community around the Nurul Huda Gantar Mosque, sampling using a purposive sampling technique, namely a sampling technique with certain considerations. Collecting data using observation, interviews, and direct teaching. The research results obtained are the Integrity of the Dai in conveying da'wah at the Nurul Huda Gantar Mosque Study. Therefore, apart from having to have extensive knowledge and qualified professional competence, strong personality integration will be an important factor influencing the success of a da'wah. Factors supporting the Dai in conveying da'wah at the Nurul Huda Gantar Mosque Study are the competence and knowledge possessed by the Dai. The preachers at the Nurul Huda Gantar Mosque have experience in preaching, and sufficient religious education. Meanwhile, the inhibiting factors for the Dai in conveying da'wah at the Nurul Huda Gantar Mosque are inadequate facilities, coupled with the construction and development of the Nurul Huda Gantar Mosque which is running slowly. Thus resulting in less than the maximum of the preachers to preach.